Prevalence of tick species in goats in the District of Sibi, Pakistan - Rehman, Fazal Ur (Archives of Veterinary Science, 2025)
Globally, tick infestation and tick-transmitted diseases affect the health of domestic species and cause huge economic losses. The current study investigated the prevalence of tick species in the goat population in the District of Sibi, Province of Balochistan, Pakistan. A total of six villages were selected, three from Tehsil Sibi: i) Khajjak, ii) Kurak, iii) Marghazani, and three from Tehsil Lehri; i) Taro Laal Shah, ii) Trihaar, and iii) Tehri Behramani. A total of 300 animals (50/village) were randomly selected. The prevalence of ticks associated with age, gender, and various housing systems was recorded. Tick samples were collected, processed for morphological examination under stereomicroscope, and mounted for gross identification. The data was analyzed using the Chi-square test, Fisher’s exact test using SPSS software, and MS Excel frequency distribution. A total of 198 animals were found infested with ticks, resulting in an overall prevalence of 66%. Specifically, 150 animals were examined from each Tehsil, with 96 and 102 animals infested with ticks in the Sibi and Lehri tehsils, respectively, resulting in 64.0 and 68.0% prevalence rates. The prevalence of ticks in Khajjak, Kurak, and Marghazani villages was recorded as 33.0, 29.0, and 34.0%, respectively. The prevalence of tick infestation in Taro Lal Shah, Trihaar, and Tehri villages was 35.0, 30.0, and 37.0%, respectively. The gender, age, and type of housing system showed an overall tick prevalence of 66.0%. In the present study, Amblyomma variegatum (50%), Rhipicephalus sanguineus (35%), and Hyalomma truncatum (15%) were observed. The prevalence of ticks was associated with risk factors such as sex (females) and age (old age) of goats, as well as housing (mud-type) systems. The study focused on tick prevalence, emphasizing the importance of tick control, production, and the prevention of tick-borne diseases. This is the first report on the prevalence of ticks in goats in the Sibi District of Balochistan, Pakistan.